Heat‐killed Salmonella typhimurium mitigated radiation‐induced lung injury. (7th August 2019) - Kun, Cao; Tao, Luo; Leiyuan, Hu; Yunhao, Fang; Ning, Wu; Zhe, Liu; Yuanyuan, Chen; Xiao, Lei; Hongran, Qin; Jianming, Cai; Fu, Gao; Yanyong, Yang
Abstract: Radiation‐induced lung injury (RILI) is a serious complication in thoracic tumour radiotherapy. It often occurs in clinical chest radiotherapy and acute whole‐body irradiation (WBI) caused by nuclear accidents or nuclear weapon attack. Some radioprotective agents have been reported to exert protective effects when given prior to radiation exposure, however, there is no treatment strategy available for preventing RILI. In this study, we demonstrated that heat‐killed Salmonella typhimurium (HKST), a co‐agonist of Toll‐like receptors 2 (TLR2), Toll‐like receptors 4 (TLR4) and Toll‐like receptors 5 (TLR5), mitigated radiation‐induced lung injury through the transforming growth factor‐β (TGF‐β) signalling pathway. We found that HKST alleviated lung hyperaemia and pathological damage after irradiation, indicated that HKST inhibits the early inflammatory reaction of radiation‐induced lung injury. Then, for the first time, we observed HKST reduced collagen deposit induced by irradiation in the later phase (7‐14 week) of RILI, and we found that HKST inhibited radiation‐induced cell apoptosis in lung tissues. We found that HKST reduced the level of TGF‐β and regulated its downstream signalling pathway. Finally, it was found that HKST inhibited radiation‐induced epithelial–mesenchymal transition (EMT) in lung tissues. In conclusion, our data showed that HKST effectively mitigated RILI through regulating TGF‐β, provide novel treatment strategy for RILI in whole‐body irradiation and radiotherapy.